Anomalous cross field electron transport in a Hall effect thruster - Boniface, C.; Garrigues, L.; Hagelaar, G. J. M.; Boeuf, J. P.; Gawron, D.; Mazouffre, S. (Applied physics letters, 2006)
The origin of anomalous electron transport across the magnetic field in the channel of a Hall effect thruster has been the subject of controversy, and the relative importance of electron-wall collisions and plasma turbulence on anomalous transport is not clear. From comparisons between Fabry-Pérot measurements and hybrid model calculations of the ion velocity profile in a 5 kW Hall effect thruster, we deduce that one and the same mechanism is responsible for anomalous electron transport inside and outside the Hall effect thruster channel. This suggests that the previous assumption that Bohm anomalous conductivity is dominant outside the thruster channel whereas electron-wall conductivity prevails inside the channel is not valid.